A quantitative method for measuring innate phagocytosis by human monocytes using real‐time flow cytometry. Issue 4 (16th October 2013) - Gu, Ben J.; Sun, Chun; Fuller, Stephen; Skarratt, Kristen K.; Petrou, Steven; Wiley, James. S.
Abstract Phagocytosis is central to immunity however a rapid and standardized method is much needed for quantitative assessment of the phagocytic process. We describe a real‐time flow cytometric method to quantitate the phagocytosis of fluorescent latex beads by human monocytes in serum‐free conditions. Effects of buffer composition, temperature, pH, and bead surface on phagocytic rate are described. The innate phagocytic ability of human monocytes from single subjects measured by this method was relatively stable over many months although phagocytosis rate varied as much as two‐fold between individuals. Comparable results were obtained with a simplified method using several mL of whole blood which is suitable for routine clinical application. This method also allows two‐color flow cytometric measurement of cytosolic calcium levels during the phagocytic uptake of fluorescent beads. © 2013 International Society for Advancement of Cytometry